A recent change in the relation between women's income and childbirth: heterogeneous effects of work-family balance policy. (6th September 2022) - Chung, Min-Su; Lee, Keunjae
Abstract: It has been widely perceived in South Korea that the rise in a woman's income is negative for her childbirth. This study tries to verify the hypothesis empirically because the Korean government initiated the basic plan for low fertility in 2006 and has constantly strengthened work–family balance policy since then. Our analysis using a household annual data over 18 years, 1999–2016, indicates that married women's economic power relates positively to childbirth for the period after 2006. We also find that the higher birth likelihood among top income quartile women is largely attributed to their better accessibility to maternity protection benefits. These findings imply that the government's efforts to support work–family balance have been successful to a certain extent. However, the benefits remain limited only to high-income women.